1987
DOI: 10.1073/pnas.84.16.5863
|View full text |Cite
|
Sign up to set email alerts
|

RNA splicing permits expression of a maize gene with a defective Suppressor-mutator transposable element insertion in an exon.

Abstract: The bz-mJ3CS9 allele of the bronze-1 gene in maize contains a 902-base-pair defective Suppressor-mutator (dSpm) transposable element in the second exon. Nevertheless, 40-50% of the enzymatic activity conditioned by a nonmutant allele at the bronze-1 locus is routinely recovered in crude extracts prepared from plants carrying bz-mJ3CS9 in the absence of an autonomous Suppressor-mutator element. Analyses of RNAs produced by such plants show that transcription proceeds through the dSpm. The dSpm sequence of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 26 publications
1
39
0
Order By: Relevance
“…(ii) In the case of a cauliflower mosaic virus strain which contains a mutation resulting in a partial processing of the cauliflower mosaic virus 35S RNA (in the wild-type strain the 35S RNA does not appear to be spliced), it is one of the most A+U-rich RNA regions that is spliced out (18). (iii) Transposable element sequences located in the coding regions of different maize genes are frequently spliced out, partially restoring a wild-type phenotype (21,44,47,51). In most instances, the A+U content of these sequences is high.…”
mentioning
confidence: 99%
“…(ii) In the case of a cauliflower mosaic virus strain which contains a mutation resulting in a partial processing of the cauliflower mosaic virus 35S RNA (in the wild-type strain the 35S RNA does not appear to be spliced), it is one of the most A+U-rich RNA regions that is spliced out (18). (iii) Transposable element sequences located in the coding regions of different maize genes are frequently spliced out, partially restoring a wild-type phenotype (21,44,47,51). In most instances, the A+U content of these sequences is high.…”
mentioning
confidence: 99%
“…Earlier work with bzl-ml3 and its derivatives suggested that AS-1 splicing produced functional enzyme (Kim et al, 1987). This was based on the observation that splicing at AS-1 maintains the open reading frame.…”
Section: As-1 Splicing 1s Responsible For Enzymic Activitymentioning
confidence: 99%
“…Sequences from CS-9 (Kim et al, 1987) and bzl-R (Ralston et al, 1988) have been reported. Alleles used for flavonol 03-glucosyltransferase (UFGT) assays were in a genetic background containing B and PI to boost expression of BZ7 in husk tissue.…”
Section: Plant Materials and Nucleic Acid Lsolationmentioning
confidence: 99%
See 2 more Smart Citations